Dimensi Konseling Islami dalam Praktek Psikologi Pembebasan Emosi-Spiritual - Tajiri, Hajir (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2009)
There is similarity of form and even available kink of practice flank among psychology (SEFT) and Islamic counselling. Both gets effort to give helping service to solute individual problemsâs. That kink even SEFT that rely body energy exploit in reality doesnt come to separate its-self of psychology aspects. Besides technical step that utilized by SEFT apparently gets counselling dimension. Its indication, SEFT is seen not effective when thoughts concentration and perceives focus not been ballasted with spirituals force. Condition of thoughts and perceives tasted in line with spirituals force principle namely khusyus attitude, sincere and defenseless that for that matter so familiar at world counselling specified in Islamic counselling.Â Â